Bilateral Cricoarytenoid Arthritis: A Cause of Recurrent Upper Airway Obstruction in Rheumatoid Arthritis - Pradhan, Pradeep (Malays J Med Sci, 2016)
We report a case of bilateral cricoarytenoid joint arthritis with history of rheumatoid arthritis, presented with stridor to the outpatient department. Endolaryngoscopy revealed adducted vocal cords and a nodule over left arytenoid which later confirmed to be rheumatoid nodule on histopathologic examination. Initially, although patient responded well to medical treatment, recurrence was noticed after 6 months follow-up.